The Effect of Public Service Quality on Public Satisfaction with Administrative Services at the Palupi Village Head Office - Andi Muh. Ridho; Ponirin Ponirin; Umar Syarifudin; Sriwanti Sriwanti (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study analyzes the effect of public service quality on community satisfaction at the Palupi Village Head Office. The study used a quantitative approach with 90 respondents selected through purposive sampling method. The main instrument is a questionnaire that includes five dimensions of service quality: Tangibles, Responsiveness, Reliability, Assurance, and Empathy. Data analysis was carried out by multiple linear regression. The results showed that all dimensions of service quality have a significant influence on community satisfaction, with the contribution of independent variables amounting to 94.6%. The Empathy variable has the greatest influence, followed by Reliability. This study recommends increasing the professionalism of the apparatus and innovation in administrative services to increase public trust in the government.